16 Feeding practices in paediatric Burkitt's Non-Hodgkin's lymphoma with mucositis: a retrospective chart review. (30th November 2020) - Gardiner, Breeana; Taylor, Louise; Renshaw, Gemma; Illingworth, Sarah; OConnor, Graeme
Abstract : Background: Mucositis is a severe side effect of chemotherapy and can increase the risk of malnutrition in childhood cancer. There are no evidence-based guidelines for the optimal nutritional management for children who develop mucositis. The aim of this study was to determine and compare any associations between days on naso-gastric (NG) tube feeding, days on parenteral nutrition (PN) and weight z-scores in children who experienced mucositis. Method: Retrospective data was collected from medical records at Great Ormond Street Hospital (GOSH). Children <16 years of age who received two cycles of Cyclophosphamide, Vincristine, Prednisone, Doxorubicin and Methotrexate (COPADM) chemotherapy for Burkitt's Non-Hodgkin's Lymphoma (BNHL) between May 2015 and August 2019 were included. Results: Participants included 18 males and 4 females (average age of 6 years). During COPADM1, 90% developed mucositis (n20) and 100% during COPADM2 (n22). Including both COPADM cycles, 20% (n9) received only NG feeds, 29% (n13) received only PN, 29% (n13) received a combination of NG feeds and PN and 20% (n9) had oral intake and oral nutrition support. The average weight loss from admission to discharge was 1.67 kg. Weight loss appeared to be less in patients who received NG feeds in combination with PN (-0.38 kg) compared to those receiving NG (-1.93 kg) or PN (-0.98 kg) separately. No significant correlation was found between days spent on NG feeds and days on PN during COPADM 1 (r = 0.63; p = >0.05) or COPADM 2 (r = 0.86; p = >0.05). Conclusion: NG feeding appears not to influence days on PN in this patient group. However, where PN use is necessary, using complementary NG feeding may reduce weight loss in BNHL paediatric patients. A well-planned, intervention study is needed comparing NG and PN use in children being treated with mucositis-inducing chemotherapy, and the impact feeding methods may have on patient outcomes.